(untitled) (SETARA : Jurnal Ilmu Hukum, 2022)
Terrorists have penetrated people’s lives like a virus, and terrorism has spread for decades across various groups in Indonesia. Whereas in the past this spread exploited educational institutions and places of worship, the presence of social media now makes the transmission of radicalism much easier. Radical ideas are instilled by terrorist groups through propaganda conducted in a closed and systematic manner, making detection and prevention difficult for security forces. This study examines how to counter the spread of radical propaganda through social media. The research aims to identify and analyze countermeasures against the spread of radical propaganda through social media. The method used is normative juridical research. Laws and regulations together with various forms of literature serve as the materials for this research. The study finds that strict criminal sanctions for the spread of radical propaganda through social media are not expressly provided in the Counterterrorism Law, and current efforts remain focused on repressive law enforcement. Densus 88 AT cannot effectively enforce the law against actors spreading radical propaganda who have not yet committed acts of terrorism. Through non-penal means, counterterrorism begins with cyber patrols conducted by BNPT and the Police in cooperation with the Ministry of Communication and Information to take down radical propaganda content on social media.